Fractionation of hydrogen isotopes in lipid biosynthesis - Sessions, A. L.; Burgoyne, T. W.; Schimmelmann, A.; Hayes, J. M. (Organic Geochemistry, 1999)
Isotopic compositions of carbon-bound hydrogen in individual compounds from eight different organisms were measured using isotope-ratio-monitoring gas chromatography-mass spectrometry. This technique is capable of measuring D/H ratios at natural abundance in individual lipids yielding as little as 20 nmol of H-2, and is applicable to a wide range of compounds including hydrocarbons, sterols, and fatty acids. The hydrogen isotopic compositions of lipids are controlled by three factors: isotopic compositions of biosynthetic precursors, fractionation and exchange accompanying biosynthesis, and hydrogenation during biosynthesis. delta D values of lipids from the eight organisms examined here suggest that all three processes are important for controlling natural variations in isotopic abundance. n-Alkyl lipids are depleted in D relative to growth water by 113-262 parts per thousand, while polyisoprenoid lipids are depleted in D relative to growth water by 142-376 parts per thousand. Isotopic variations within compound classes (e.g., n-alkanes) are usually less than similar to 50 parts per thousand, but variations as large as 150 parts per thousand are observed among isoprenoid lipids from a single organism. Phytol is consistently depleted in D by up to 50 parts per thousand relative to other isoprenoid lipids. Inferred isotopic fractionations between cellular water and lipids are greater than those indicated by previous studies. (C) 1999 Elsevier Science Ltd. All rights reserved.
254efTimes Cited:281Cited References Count:26